Implementation Management Budget Eat Students for Fulfil Nutrition Students at PINK 03 Islamic Boarding School - H. Soro , Suharyanto; Zulfikar, Muhammad; Ridwanullah, Feisal Leonard (Civiliza Publishing, Indonesia., 2025)
Study This analyze implementation management budget Eat students in effort fulfil need nutrition at PINK 03 Islamic Boarding School. With use approach qualitative through method studies case, research This involving four representative informants​ various stakeholders, namely administrator Islamic boarding school, administrator kitchen, students male and female students. Data collected through interview in-depth and analyzed use technique analysis thematic . Research results show that Islamic boarding school has allocate significant budget​ For Eat students, namely Rp. 400,000-450,000 from SPP of Rp. 1,000,000 per student per month, with a total budget Eat reaching Rp. 80-90 million per month for 200 students. System management adhere to centralization with control strict, supported by an adaptive procurement strategy through purchases in traditional markets, partnerships with suppliers, and purchasing in amount big. Challenge main issues faced covering fluctuations price material food, limitations menu diversification, and inconsistency quality of taste. Although thus, students show level sufficient satisfaction​ good and condition stable health. Research​ conclude that management budget eating at the Islamic boarding school has walk Enough effective However Still need optimization in aspect long-term menu planning length, standardization of processing processes, and diversification source nutrition for increase quality fulfillment need nutrition students.